Menguasai Nahwu dan Shorof: Fondasi Penting dalam Pembelajaran Bahasa Arab Modern di Sekolah Dasar - Mas'ud; Syifaul Adhimah (Matluba: Jurnal Pendidikan Bahasa dan Budaya Arab, 2024)
This research explores the effectiveness of teaching Nahwu and Shorof in Arabic language learning at elementary schools using thematic approaches and interactive technology. The results show a significant improvement in students' Arabic language abilities, as well as positive experiences from both teachers and students. The post-test scores were significantly higher than the pre-test scores, indicating the effectiveness of the new teaching methods. Interviews and classroom observations revealed that thematic and technological approaches make learning more engaging and relevant, thus enhancing students' motivation and participation. Teachers reported that despite the challenges in preparing materials and using technology, the benefits were substantial. The study suggests practical recommendations for integrating thematic and interactive technological approaches into the curriculum to make Arabic language learning more engaging and effective. However, it highlights the need for adequate support from schools, including preparation time, professional training for teachers, and access to technological devices. Overall, the study concludes that with the right approach and sufficient support, teaching Nahwu and Shorof can provide a solid foundation in Arabic language learning, helping students not only master the language but also develop critical and analytical thinking skills through a deep understanding of grammar.